Bacterial Reductive Dissolution of Crystalline Fe(III) Oxide in Continuous-Flow Column Reactors - Roden, Eric E. (American Society for Microbiology, 2000)
Bacterial reductive dissolution of synthetic crystalline Fe(III) oxide-coated sand was studied in continuous-flow column reactors in comparison with parallel batch cultures. The cumulative amount of aqueous Fe(II) exported from the columns over a 6-month incubation period corresponded to (95.0 ± 3.7)% (n = 3) of their original Fe(III) content. Wet-chemical analysis revealed that only (6.5 ± 3.2)% of the initial Fe(III) content remained in the columns at the end of the experiment. The near-quantitative removal of Fe was visibly evidenced by extensive bleaching of color from the sand in the columns. In contrast to the column reactors, Fe(II) production quickly reached an asymptote in batch cultures, and only (13.0 ± 2.2)% (n = 3) of the Fe(III) oxide content was reduced. Sustained bacterial-cell growth occurred in the column reactors, leading to the production and export of a quantity of cells 100-fold greater than that added during inoculation. Indirect estimates of cell growth, based on the quantity of Fe(III) reduced, suggest that only an approximate doubling of initial cell abundance was likely to have occurred in the batch cultures. Our results indicate that removal of biogenic Fe(II) via aqueous-phase transport in the column reactors decreased the passivating influence of surface-bound Fe(II) on oxide reduction activity, thereby allowing a dramatic increase in the extent of Fe(III) oxide reduction and associated bacterial growth. These findings have important implications for understanding the fate of organic and inorganic contaminants whose geochemical behavior is linked to Fe(III) oxide reduction.